Correlation Between Knowladge and Family Support with Antenatal Care Service Utilization in Covid 19 Pandemic - Melly Melly; Magdalena Magdalena; Kurniawati Kurniawati (Poltekkes Kemenkes Riau, 2023)
Ante Natal Care (ANC) service is a health service activity carried out from the time of conception until before the start of the birth process. ANC examinations that are not carried out regularly can cause problems in pregnancy, both for the mother and the fetus in the form of morbidity and mortality. The research objective was to determine the relationship between husband's knowledge and support and utilization of ANC services in pregnant women. The research design used is descriptive analytic with a cross sectional design using a questionnaire. with a total sample of 40 pregnant women. The results of this study were that there was a significant relationship between knowledge and family support with the use of ANC services for pregnant women with a p-value of 0.002 <a = 0.05 and a p-value of 0.032 <a = 0.05. Health workers are expected to increase health counseling and promotion on a regular basis regarding the importance of regular prenatal checks so that they can increase their knowledge about prenatal checks for pregnant women.